Awareness, knowledge, and barriers to low vision services among eye care practitioners in Maharashtra - Dilkash, Mantasha; Banerjee, Susmita; Dubey, Gaurav; Kumari, Vibha; Kumari, Ragni; Gupta, Deepak (International Journal of Research in Medical Sciences, 2021)
Background: Visual impairment is an important global health issue. 90% of the world’s blind people reside in underdeveloped countries. According to population-based statistics, India has the most visually impaired persons (about 9 million). The world health organization (WHO) estimates that 285 million people worldwide are blind or have impaired eyesight. Hence it is necessary to have information about knowledge and awareness of low vision services among eye care practitioners to improve the low vision care in the world. Methods: A prospective cross-sectional survey was done at Dr. D. Y. Patil medical college and research centre (Ophthalmology department) between eye care practitioners practicing in Maharashtra, India, through a pre-tested standardized questionnaire. Results: In this study, retinal problems (76.1%) and glaucoma (11.1%) were reported as two major causes of low vision. Provision of best spectacle correction, rehabilitation, and referral to other hospitals/specialized centers was considered by 31.7%, 4.7%, and 23.8% practitioners, respectively. Magnifiers were found to be the most commonly prescribed low vision device (73%). Conclusions: Low eyesight is a big health issue all over the world. Low vision services assist patients in improving and maintain their functional vision. It also enhances the quality of life and everyday living skills. There are many barriers and a lack of understanding about low vision services. They assess eye care providers’ awareness, knowledge, and challenges to poor vision services in Maharashtra. This study results showed a lack of awareness (33.3%) and training (33.3%) among the practitioners were the significant barriers restricting low vision services.